2011
DOI: 10.1073/pnas.1010059108
|View full text |Cite
|
Sign up to set email alerts
|

Glass-like dynamics of collective cell migration

Abstract: Collective cell migration in tissues occurs throughout embryonic development, during wound healing, and in cancerous tumor invasion, yet most detailed knowledge of cell migration comes from single-cell studies. As single cells migrate, the shape of the cell body fluctuates dramatically through cyclic processes of extension, adhesion, and retraction, accompanied by erratic changes in migration direction. Within confluent cell layers, such subcellular motions must be coupled between neighbors, yet the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
739
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 703 publications
(788 citation statements)
references
References 35 publications
45
739
3
1
Order By: Relevance
“…As we and others [16,52] have noted, active tissues display glassy dynamics: the motion of individual cells is constrained because they are surrounded by tightly packed neighbouring cells that impede their progress. It has been shown that the dynamics in non-biological glassy or jammed materials display universality: dynamical features do not depend on the details of the interactions [53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we and others [16,52] have noted, active tissues display glassy dynamics: the motion of individual cells is constrained because they are surrounded by tightly packed neighbouring cells that impede their progress. It has been shown that the dynamics in non-biological glassy or jammed materials display universality: dynamical features do not depend on the details of the interactions [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers have discovered that some two-dimensional tissues exhibit glassy behaviour [16,17]. In these confluent tissues, individual cells have difficulty moving past one another or exchanging neighbours, resulting in a 'frozen' system with a macroscopic response that is solid-like even on long timescales.…”
Section: Introductionmentioning
confidence: 99%
“…As q is decreased, S 0 (q) is characterised by a pronounced dip, indicating the presence of mesoscopic-scale inhomogeneities in the cell distribution, or clustering [ 32,36]. It is worth noting that this feature cannot appear in equilibrium systems without invoking attractive interactions and for this reason in active systems, one speaks of non-equilibrium clustering.…”
Section: Control Cellsmentioning
confidence: 99%
“…RAB5A is a master regulator of the endocytic activity of the cell and it plays an important role in the dissemination of aggressive breast tumours [38,39,40]. In control monolayers, cell density increases due to mitotic division, which causes a near complete kinetic arrest akin to a jamming or rigidity transition [32,41]. We have recently shown that, under these latter conditions [42], the elevation of RAB5A reawakens the motility of kinetically arrested monolayer, by promoting a flocking transition accompanied by the emergence of large-scale, collective, directed migration patterns [43,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation